PENGARUH HARGA, KUALITAS PRODUK, DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN GAG PTC SURABAYA - Yohans, Silvia; Aurelia, Jennifer; Sutanto, J.E. (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
The study aims to analyze the impact of price, product quality, and service quality on purchase decisions at GAG PTC Surabaya. This research employs a quantitative approach, with data collected through offline questionnaire distribution. The sample consists of 170 respondents who meet the criteria of having purchased products at GAG PTC Surabaya at least twice and being between 17 and 55 years old. The sampling technique employed is non-probability sampling using a purposive sampling approach. The data analysis is conducted using multiple linear regression analysis. The findings of this study indicate that: (1) price has a significant influence on the purchase decision of GAG products, (2) product quality significantly affects the purchase decision of GAG products, and (3) service quality also has a significant impact on the purchase decision of GAG products.